2022
DOI: 10.1093/gji/ggac306
|View full text |Cite
|
Sign up to set email alerts
|

Distributional finite-difference modelling of seismic waves

Abstract: Summary This study introduces a Distributional finite-difference Method (DFDM) for modeling the propagation of elastic waves in heterogeneous media in the time domain. DFDM decomposes the modeling domain into multiple elements that can have arbitrary sizes. When large elements are used, the proposed method closely resembles the finite-difference method because the wavefield is updated using operations involving band diagonal matrices only. Thus DFDM is computationally efficient. When smaller ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 90 publications
0
31
0
Order By: Relevance
“…A review of these popular modeling methods is carried out in Virieux et al (2011). Recently, Masson (2022) proposed a distributional finite-di↵erence method, denoted by the DFD keyword thereafter. The DFD approach lies somewhere between the pseudo-spectral/finite-di↵erence methods and the finite/spectralelement methods and combines some desirable features of the former methods in a relatively simple manner.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of these popular modeling methods is carried out in Virieux et al (2011). Recently, Masson (2022) proposed a distributional finite-di↵erence method, denoted by the DFD keyword thereafter. The DFD approach lies somewhere between the pseudo-spectral/finite-di↵erence methods and the finite/spectralelement methods and combines some desirable features of the former methods in a relatively simple manner.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, special care must be taken to eliminate spurious(non-physical) parasitic modes (see, e.g., New et al, 1998), for example, the odd-even decoupling observed when using centered finite-di↵erence operators. In Masson (2022) a MacCormack type of scheme is proposed to address this issue (see e.g., Zhang and Chen, 2006). In this study, we consider an alternative approach where the bases representing the wavefield are analogous to the staggered grid in which the variables are not defined at the same position (as opposed to the collocated grid).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations